Daphnetin Protects Schwann Cells Against High-Glucose-Induced Oxidative Injury by Modulating the Nuclear Factor Erythroid 2-Related Factor 2/Glutamate–Cysteine Ligase Catalytic Subunit Signaling Pathway - Chih-Yuan Ko; Run-Tian Meng; Chung-Hsin Wu; Thi Kim Ngan Nguyen; Yu-En Chen; James Swi-Bea Wu; Wen-Chung Huang; Szu-Chuan Shen (Plants)
Diabetic peripheral neuropathy (DPN), a common complication of diabetes mellitus, is primarily characterized by damage to Schwann cells caused by oxidative stress under hyperglycemic conditions. Recently, we demonstrated the ability of coumarin-rich Ficus formosana Maxim. to alleviate DPN in ovariectomized diabetic mice. However, the underlying mechanisms remain unclear. In this study, we established an in vitro DPN model using RSC96 Schwann cells exposed to high glucose levels. Daphnetin, a natural coumarin found abundantly in Ficus formosana Maxim., was co-incubated with Schwann cells in a high-glucose medium to investigate its protective effects against DPN. The free radical scavenging capacity of daphnetin was evaluated, along with assessments of cell viability, apoptosis, H2O2 levels, and the expression of proteins by the nuclear factor erythroid 2-related factor 2 (Nrf2)/glutamate–cysteine ligase catalytic subunit (GCLC) pathway in RSC96 Schwann cells. The results showed that daphnetin was non-toxic within the tested concentration range of 6.25 μM to 50 μM in RSC96 Schwann cells. Moreover, daphnetin significantly improved cell viability, exhibited strong antioxidant activity, reduced H2O2 levels, and regulated the Nrf2/GCLC pathway protein expressions in RSC96 cells cultured in high-glucose medium. Additionally, daphnetin influenced apoptosis-related proteins by decreasing the expression levels of Bax and Caspase 3, while increasing the Bcl-2 expression level in high-glucose-treated RSC96 cells. These findings suggest that daphnetin may alleviate oxidative stress induced by high glucose levels through activation of the Nrf2/GCLC pathway and inhibition of Schwann cell apoptosis, underscoring its potential as a therapeutic agent for DPN.